The DEVELOPMENT OF A METHODOLOGY FOR TEACHING TECHNICAL SUBJECTS IN MILITARY PERSONNEL TRAINING - Amirova Zarifa Fayzilloyevna (Journal of Education, 2026)
The article talks about technologies for the formation of technical thinking among cadets of engineering specialties of military education in the process of teaching technical sciences.